KINDERGARTEN TEACHERS’ NOTIONS OF PARENT INVOLVEMENT AND PERCEIVED CHALLENGES - Preston, Jane P.; MacPhee, Mary M.; Roach O’Keefe, Alaina (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
We examine how kindergarten teachers on Prince Edward Island depict both parent involvement in school and its perceived challenges. Data consisted of written responses to two open-ended survey questions completed by 62 participants or 94% of the kindergarten teachers on PEI. Results showed that teachers recognized parent involvement in traditional forms. Barriers included lack of educator time and unproductive school policies. Extending from Epstein’s parent involvement model, if increasingly rich forms of parent involvement are to actualize, educators must be attuned to family vibrancy — the diverse gifts each family possesses; family vibrancy includes the belief that every parent, regardless of socioeconomic status, language abilities, ethnicity, religion, etc., can and does support his/her child’s education to the best of his/her ability.